1999
DOI: 10.2527/1999.7771654x
|View full text |Cite
|
Sign up to set email alerts
|

Novel insight into the control of litter size in pigs, using placental efficiency as a selection tool.

Abstract: Chinese Meishan pigs produce three to five more pigs per litter than less-prolific U.S. or European pig breeds as a result of a markedly decreased placental size and an increased pig weight: placental weight ratio (placental efficiency). We hypothesized that as a result of their intense selection for prolificacy, the Chinese had indirectly selected for a smaller, more efficient placenta in the Meishan breed. The goals of this study were to determine whether 1) significant variation in placental size and effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
134
2
4

Year Published

2000
2000
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(149 citation statements)
references
References 20 publications
9
134
2
4
Order By: Relevance
“…Importantly, the size and functional capacity of the placenta, and uteroplacental transfer of materials between mother and fetus, were the major factors to affect embryonic/fetal growth and development (Bazer et al 1969;Gude et al 2004;Wu et al 2006Wu et al , 2010. Previous reports have shown that placental efficiency affects litter size and that placental size is highly correlated with fetal weight after day 60 of gestation in swine (Biensen et al 1998;Wilson et al 1999). Another interesting and novel finding of the present work is that dietary arginine supplementation enhanced placental weight per sow (Table 2), indicating an increase in total placental growth.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the size and functional capacity of the placenta, and uteroplacental transfer of materials between mother and fetus, were the major factors to affect embryonic/fetal growth and development (Bazer et al 1969;Gude et al 2004;Wu et al 2006Wu et al , 2010. Previous reports have shown that placental efficiency affects litter size and that placental size is highly correlated with fetal weight after day 60 of gestation in swine (Biensen et al 1998;Wilson et al 1999). Another interesting and novel finding of the present work is that dietary arginine supplementation enhanced placental weight per sow (Table 2), indicating an increase in total placental growth.…”
Section: Discussionmentioning
confidence: 99%
“…the ratio of fetal weight to placental weight). Significant improvement has not occurred [11,12]. Nutritional studies (improved diet balance or vitamin supplementation) also failed to show consistent beneficial effects [13,14].…”
Section: Prenatal Mortality In Commercial Meat Pigsmentioning
confidence: 99%
“…However, placental growth and development of its functional ability are important because they are the means by which the foetus receives metabolic substrates for growth. So selection on placental size and efficiency may provide a valuable tool for optimizing litter size in commercial livestock, such as swine and sheep (Wilson et al 1999;Mesa et al 2012). In our study, there is no significant difference on placental efficiency among three goat breeds with different prolificacy.…”
Section: Discussionmentioning
confidence: 99%